Empowering Women Worker’s Group Through Mentoring Management, Innovation, and Branding Product of Pants Convection - Muhammad Idlom Dzulqarnain; Husni Tamrin; Azzah Nor Laila; Hardiyanto Hardiputra (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2022)
Pants convection is a home business from cloth in the village of Sukosono, Jepara. The community of mothers and teenagers are interested in entrepreneurship and work in the convection sector because they tend to be more flexible and can be done at home. A large number of workers and the production of the pants convection are not matched by management, product innovation, and marketing strategies. This resulted in a buildup of products, but reduced market demand. This service program aims to assist business management, as well as increase the creativity of workers in creating innovations, branding, and marketing methods so that confectionery products can compete in the market. Partners in this service are pants convection entrepreneurs in the village of Sukosono, Jepara. The method of this community service was Asset Based Community Development (ABCD), starting from the step of discovery, design, dream, define through a survey on the community. Then the step destiny through training, assistance with product brand design and marketing, then step reflection through monitoring and evaluation. The results of this assistance show that the community has an awareness of the importance of product innovation, branding, and improving the marketing system. In the product aspect, this assistance resulted in innovative pants made of woven materials, product brand logos with the name of clothing houses, and marketing through marketplaces.